Beyond metallocenes - Patil, Abhimanyu O. (American Chemical Society, 2003)
This research has yielded extraordinary results such as catalysts with activities as high or higher than those of conventional metallocenes, stereospecific and living polymerizations, and amazing new polymer structures such as highly-branched ethylene homopolymers